Izmir Mental Health Cohort for Gene-Environment Interaction in Psychosis (TürkSch): Assessment of the Extended and Transdiagnostic Psychosis Phenotype and Analysis of Attrition in a 6-Year Follow-Up of a Community-Based Sample - Kırlı, Umut; Binbay, Tolga; Elbi, Hayriye; Drukker, Marjan; Kayahan, Bülent; Özkınay, Ferda; Onay, Hüseyin; Alptekin, Köksal; van Os, Jim (Frontiers in Psychiatry, 2019)
Objective: TürkSch is a prospective, longitudinal study in a representative community sample (İzmir, Turkey), consisting of several data collection stages, in order to screen and follow-up mental health outcomes with a special focus on the extended and transdiagnostic psychosis phenotype. The aim of the present paper is to describe the research methodology, data collection results and associations with non-contact and refusal in the longitudinal arm. Methods: Households were contacted in a multistage clustered probability sampling frame covering 11 districts and 302 neighborhoods at baseline (n=4011) and at 6-year follow-up (n=2185). Both at baseline and at follow-up, participants were interviewed with the Composite International Diagnostic Interview. Participants with probable psychotic disorder were re-interviewed with the SCID-I either at the hospital or the participant’s residence. Relevant neighborhood-level measures were assessed in a separate sample (n=5124) in addition to individual-level measures. Candidate gene-by-environment interactions were investigated using two nested case-control studies. Results: Individuals with a mental health problem had lower refusal rates. Older and lower educated individuals had a lower probability of non-contact. Discussion: The TürkSch study has an advanced design, in order to meet the challenges of evaluating the multidimensional etiological and phenomenological nature of the extended and transdiagnostic psychosis phenotype